Study the impact of the COVID-19 pandemic on the construction industry in Egypt. (January 2022) - Mohamed Elnaggar, Shereen; Elhegazy, Hosam
Abstract: This paper attempts to quantify the impact of the COVID-19 pandemic on the construction industry under different investment and economic scenarios in Egypt. The survey was conducted to assess the cost impact of the ongoing COVID-19 pandemic on the construction industry, considering essential aspects, such as manpower, plant and machinery, and material, and their net effect on overall construction cost. The recommendations covered in this paper address many such measures under short, medium, and long-term categories. These measures underline the need to improve systems and processes for adequately responding to the current changing environment and effectively confronting such disruptions in the future. In addition, the paper serves as a start to thinking about the study of procedures during a future pandemic to inhibit any impact on the project timeline or personnel health.